2013
DOI: 10.1111/2041-210x.12034
|View full text |Cite
|
Sign up to set email alerts
|

SURFACE: detecting convergent evolution from comparative data by fitting Ornstein‐Uhlenbeck models with stepwise Akaike Information Criterion

Abstract: Summary1. We present a method, 'SURFACE', that uses the Ornstein-Uhlenbeck stabilizing selection model to identify cases of convergent evolution using only continuous phenotypic characters and a phylogenetic tree. 2. SURFACE uses stepwise Akaike Information Criterion first to locate regime shifts on a tree, then to identify whether shifts are towards convergent regimes. Simulations can be used to test the hypothesis that a clade contains more convergence than expected by chance. 3. We demonstrate the method wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
471
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(474 citation statements)
references
References 39 publications
2
471
0
1
Order By: Relevance
“…With sufficient data, recently developed methods for mapping trait evolution onto phylogenies [78] or for quantifying the strength of convergent evolution [79] might emerge as useful resources for identifying and measuring convergent interactions. However, to use these tools, one set of interacting partners must be redefined as a trait of interest or measure of diversity.…”
Section: Box 2 Potential Methods For Exploring Patterns Of Convergenmentioning
confidence: 99%
“…With sufficient data, recently developed methods for mapping trait evolution onto phylogenies [78] or for quantifying the strength of convergent evolution [79] might emerge as useful resources for identifying and measuring convergent interactions. However, to use these tools, one set of interacting partners must be redefined as a trait of interest or measure of diversity.…”
Section: Box 2 Potential Methods For Exploring Patterns Of Convergenmentioning
confidence: 99%
“…Similarly, the three littoral species are joined with the arboreal regime because the difference in hindlimb length alone is not significant enough to identify a separate adaptive peak. Previous simulation analyses have confirmed that SURFACE performs well with datasets that include multiple convergent traits, but instances of convergence were not always identified with single (convergent) traits [43]. Thus, even though these two rock and three littoral species significantly differ along specific trait axes from arboreal types, they have not been diagnosed as distinct.…”
Section: (B) Convergencementioning
confidence: 97%
“…We fitted a single rate BM model (BM1) and OU models with either a single optimum for all species (OU1) or with multiple optima, but single rates of selection (a) and stochastic motion around all optima (s 2 ). Secondly, we evaluated whether independent lineages converged on similar phenotypic optima by using a comparative approach implemented in R. SURFACE [43] uses a stepwise corrected AICc (Akaike's information criterion corrected for sample size) approach to fit Hansen models and evaluates the most optimal set of evolutionary regimes and regime shifts. SURFACE analyses consist of two distinct phases; a 'forward' phase during which regime shifts are added to the tree and a 'backward' phase during which shifts towards the same peaks are identified and collapsed.…”
Section: (F ) Morphological Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this approach, convergence is implied when two or more taxa have evolved to be more similar to one another than their ancestors were to each other 23 . Unlike other convergence methods like SURFACE 68 , which identify convergent shifts in selective regimes among lineages, C 1 -C 3 measure the increase in phenotypic similarity between taxa compared to that between the most divergent species in their lineages, without assuming an adaptive process. Therefore, the more dissimilar the ancestor and the more similar the descendants, the greater the strength of the convergence.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%